Analisis Efektivitas Kebijakan Subsidi Pupuk Dan Penggunaan Faktor Produksi Lahan Dan Benih Terhadap Kinerja Usahatani Padi Sawah Di Kabupaten Kerinci - Amelia, Dina; Suandi, Suandi; Wahyuni, Ira (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
Population growth in Indonesia causes the need for food to increase. The increase in food demand, especially rice originating from the rice plant, must be accompanied by an increase in production in order to achieve food security. Kerinci Regency is the center of rice production in Jambi Province. The fertilizer subsidy policy is one of the policies of the central government which is also implemented in Kerinci Regency as an effort to continue to increase rice production. However, there are several problems in the fertilizer subsidy policy, namely problems related to price, distribution, and supervision. These problems can cause fertilizer subsidy policies to run ineffectively. This study aims to describe the effectiveness of the fertilizer subsidy policy on lowland rice farming in Kerinci Regency, describe the use of land and seed production factors in lowland rice farming in Kerinci Regency, describe the performance of lowland rice farming in Kerinci Regency, and analyze the effect of the effectiveness of fertilizer subsidies, the use of factors land and seed production on the performance of lowland rice farming in Kerinci Regency. This study uses descriptive analysis and Structural Equation Model (SEM) using the PLS program. There are several problems found in the implementation of fertilizer subsidies in lowland rice farming in Kerinci Regency, namely the purchase price, and the proper use of fertilizers. Subsidized fertilizers in Kerinci Regency are always available and can be purchased by farmers in the village. The results of the SEM analysis show that the effectiveness of fertilizer subsidies, the use of land production factors, and seed production factors have a significant effect on the performance of lowland 3rice farming in Kerinci Regency